2022
DOI: 10.1002/agj2.21216
|View full text |Cite
|
Sign up to set email alerts
|

Soybean yield response to sulfur and nitrogen additions across diverse U.S. environments

Abstract: As soybean [Glycine max (L.) Merr.] yields reach record highs, more nutrients are required to maintain these production levels. This study was conducted to evaluate the effect of S and N on soybean yield in diverse environments across the United States. Data were collected from a total of 52 sites in 10 states over 2 yr (2019 and 2020) for this study. A factorial arrangement of three S rates (11, 22, and 33 kg S ha −1 ) using two sources (ammonium sulfate [AMS] and calcium sulfate [CaSO 4 ]) were broadcasted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
(49 reference statements)
2
10
0
Order By: Relevance
“…Similar to our study, previous studies comparing soil environment between responsive and nonresponsive sites have reported inconsistency in crop response to S application (DeSutter et al., 2014; Gaibor, 2021; Kaiser & Kim, 2013). Likewise, an evaluation of soybean response to S in 10 states across diverse environments found that soil and environmental factors were poor predictors of soybean yield response to S fertilization (Brooks et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our study, previous studies comparing soil environment between responsive and nonresponsive sites have reported inconsistency in crop response to S application (DeSutter et al., 2014; Gaibor, 2021; Kaiser & Kim, 2013). Likewise, an evaluation of soybean response to S in 10 states across diverse environments found that soil and environmental factors were poor predictors of soybean yield response to S fertilization (Brooks et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Studies that examine the extent and magnitude of crop response to S fertilization (e.g., Brooks et al., 2022; de Borja Reis et al., 2021; Goyal et al., 2021) should consider the application of granular P fertilizers prior to the crop being studied as a possible factor obviating the need for, or reducing crop response to, direct S fertilization. Dismissing the potential contribution of P fertilizers to satisfy the S needs of crops, seems unwise given that when applied at a rate to replace grain P removal of both crops in a corn and soybean rotation, the P fertilizers can supply 50% or more of grain S removal of the subsequent crop.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of S deficiency in the Midwest in the last 20 years (Casteel et al., 2019; Kim et al., 2013; Sawyer et al., 2015) is purported to be primarily due to the reduction in atmospheric S deposition with implementation of the USEPA Clean Air Act and its amendments enacted in 1990 (Hinckley & Driscoll, 2022; Nopmongcol et al., 2019). Despite lesser S deposition, crop response to S fertilization has been inconsistent with several studies showing infrequent responses (Brooks et al., 2022; de Borja Reis et al., 2021; Fleuridor et al., 2023). In addition to atmospheric deposition, S may be provided by the mineralization of soil organic matter (Eriksen, 2008) or the incidental application of S in other fertilizers, particularly P fertilizers (Dick et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in yield of crops will usually enhance nitrogen (N) requirements due to onward crop N demand (Adhikari et al, 2021;Brooks et al, 2022). While higher N requirements of crops are generally correlated with higher yield potential, the response to applied N also depends of the soil N status and its Abbreviations: AE, agronomic efficiency; ANR, apparent nitrogen recovery; CI, cropping intensity; DAE, days after emergence; EC, electrical conductivity; LCCI, leaf chlorophyll content index; LWP, leaf water potential; NUE, nitrogen use efficiency; SP, solute potential; SW, southwestern; SWC, soil water content.…”
Section: Introductionmentioning
confidence: 99%